2012
DOI: 10.1007/s10815-011-9698-2
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte cryopreservation in a patient with sickle cell disease prior to hematopoietic stem cell transplantation: first report

Abstract: Purpose To report the first occurrence of successful ovarian stimulation, oocyte retrieval and oocyte cryopreservation for fertility preservation in an adolescent with severe sickle cell disease scheduled to undergo a hematopoietic stem cell transplant Methods Case report Results A 19 year old female with severe sickle cell disease presented for fertility preservation counseling prior to hematopoietic stem cell transplantation. She ultimately underwent ovarian stimulation using a minimal stimulation GnRH antag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Novel methods in preserving fertility after HCT should hasten a revision of the current indications for HLA-ID sibling HCT, extending this therapeutic option to all children who have a sickle cell anemia genotype. Oocyte cryopreservation has been reported in a patient with sickle cell disease 24 . Cryopreservation of ovarian tissue is available as a research procedure, and this tissue might be utilized to restore endocrine and reproductive function after HCT 25 .…”
Section: Transplant Results In Children: Hla-id Sibling Hctmentioning
confidence: 99%
“…Novel methods in preserving fertility after HCT should hasten a revision of the current indications for HLA-ID sibling HCT, extending this therapeutic option to all children who have a sickle cell anemia genotype. Oocyte cryopreservation has been reported in a patient with sickle cell disease 24 . Cryopreservation of ovarian tissue is available as a research procedure, and this tissue might be utilized to restore endocrine and reproductive function after HCT 25 .…”
Section: Transplant Results In Children: Hla-id Sibling Hctmentioning
confidence: 99%
“…22 This strategy requires around 14 days and provides around 8 mature oocytes per cycle to cryopreserve in women with cancer, varying according to the age. [22][23][24] Previous studies showed that vitrified oocytes have a comparable outcome to fresh ones. 1,25 According to guidelines, it is the first option for adult women facing gonadotoxic treatment.…”
Section: Specific Issues and Limitationsmentioning
confidence: 99%
“…Although experience is limited, patients with SCD have success with procedures and therapies that preserve fertility. [60][61][62] Cryopreservation options have expanded and depend on stage of pubertal development. Cryopreservation of sperm in pubertal males is standard and improvement of sperm banking techniques and increased use of intracytoplasmic sperm injection may increase successful outcomes.…”
Section: Hsct and Fertility Preservationmentioning
confidence: 99%
“…Successful oocyte preservation after controlled ovarian stimulation in a 19-year-old woman with SCD has been described using a protocol to avoid hyperstimulation and incorporating anticoagulation for thrombosis prevention. 60 Although oocyte collection was successful, the patient required hospitalization for pain management postoperatively. In addition, successful pregnancies in women with SCD after ovarian tissue preservation have been reported.…”
mentioning
confidence: 99%